Animation Visualization in The Process of Making Driving Licenses Based on Multimedia in Polres District Pidie - Fathiah Fathiah; Fitriani Fitriani (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Animation movie clip in the process of making a license based driving (SIM) based on multimedia Police Pidie District serves as a medium of socialization for the community. This study aims to determine the procedure or flow in the process of making Driver's License (SIM) at Polres Pidie District and to implement multimedia applications on how to make a Driver's License (SIM) at Polres Pidie District and the community. The study was conducted at SATLANTAS Polresta Kabupaten Pidie. Making this movie clip animation has three stages of production, namely pre production, production and post production. The software used is Macromedia professional flash 8, Manga studio EX 5.0 and AVS Video Editor 7.1. The results showed that the movie clip animation about the procedure of making Driver License (SIM) is a socialization media that produces output in the form of pictures, sound and text. It is expected that animation movie clip on the process of making a driver's license (SIM) can facilitate police officers in socialize to the community and the public can better understand the procedures of making the SIM.Keywords: Animation, Interactive Application, Driver License